2010
DOI: 10.1007/s00467-009-1230-x
|View full text |Cite|
|
Sign up to set email alerts
|

Pathogenesis of Henoch-Schönlein purpura nephritis

Abstract: The severity of renal involvement is the major factor determining the long-term outcome of children with Henoch-Schönlein purpura (HSP) nephritis (HSPN). Approximately 40% children with HSP develop nephritis, usually within 4 to 6 weeks after the initial onset of the typical purpuric rashes. Although the pathogenetic mechanisms are still not fully delineated, several studies suggest that galactose-deficient IgA1 (Gd-IgA1) is recognized by anti-glycan antibodies, leading to the formation of the circulating immu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
113
0
9

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 133 publications
(127 citation statements)
references
References 82 publications
5
113
0
9
Order By: Relevance
“…[4][5][6] Similar to IgA nephropathy, increased levels of galactosedeficient IgA1 (Gd-IgA1) are detected in patients with Henoch-Schönlein purpura complicated by nephritis, and Gd-IgA1 is now believed to have a pivotal role in the pathogenesis of both IgA nephropathy and Henoch-Schö nlein purpura nephritis. 15,25 In addition, IgA-containing complexes have been found in the glomeruli of IgA nephropathy and Henoch-Schö nlein purpura nephritis patients. Furthermore, we previously showed that HenochSchö nlein purpura nephritis and IgA nephropathy had comparable prognoses when matched at presentation using propensity score analysis.…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6] Similar to IgA nephropathy, increased levels of galactosedeficient IgA1 (Gd-IgA1) are detected in patients with Henoch-Schönlein purpura complicated by nephritis, and Gd-IgA1 is now believed to have a pivotal role in the pathogenesis of both IgA nephropathy and Henoch-Schö nlein purpura nephritis. 15,25 In addition, IgA-containing complexes have been found in the glomeruli of IgA nephropathy and Henoch-Schö nlein purpura nephritis patients. Furthermore, we previously showed that HenochSchö nlein purpura nephritis and IgA nephropathy had comparable prognoses when matched at presentation using propensity score analysis.…”
Section: Discussionmentioning
confidence: 99%
“…The annual incidence of HSP has been reported to be 13.5 to 22.1 per 100,000 9−11) . While HSP is often a self -limited condition, approximately 40% of pediatric patients develop nephritis within 4 to 6 weeks of the initial presentation 12) . An age of more than 10 years at onset, persistent purpura, severe bowel angina, and relapse were identified as factors for the nephritis of HSP 13) .…”
Section: Discussionmentioning
confidence: 99%
“…Outros tratamentos específicos vão depender do surgimento de complicações como anemia mais severa, intussuscepção, hipertensão arterial sistêmica, síndrome nefrótica, insuficiência renal, artrite severa ou alterações de sensório. 4,6 O prognóstico a curto e longo prazo geralmente é excelente. Dois terços das crianças não apresentam novos episódios, o restante tem pelo menos uma recorrência normalmente quatro meses após a apresentação inicial, de menor intensidade e/ou duração.…”
unclassified
“…Menos de 1% desenvolve complicações a longo prazo, quando desenvolve geralmente é doença renal. 4 A PHS é uma vasculite leucocitoclástica associada a depósitos de IgA. Quanto à patogênese, fatores genéti-cos, ambientais e imunológicos parecem estar envolvidos, mas a causa subjacente permanece desconhecida.…”
unclassified
See 1 more Smart Citation